2010
DOI: 10.1002/rmv.668
|View full text |Cite
|
Sign up to set email alerts
|

Human anelloviruses and the central nervous system

Abstract: Torque teno virus and related anelloviruses are a recent addition to the list of agents that cause chronic productive infections and high levels of plasma viraemia in humans. Many aspects of the natural history and pathogenesis of these under many respects surprising viruses are still poorly understood. In this review, we briefly outline the general properties of anelloviruses, examine what is currently known about the interactions they establish with the central nervous system (CNS), and discuss the possible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
66
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 129 publications
(185 reference statements)
3
66
0
2
Order By: Relevance
“…Currently, human TTV is not considered to be directly associated with a particular disease, although recent studies suggested that TTV may serve as an immunological trigger of multiple sclerosis (26). Similarly, whether TTSuV is associated with a swine disease is still debatable.…”
mentioning
confidence: 99%
“…Currently, human TTV is not considered to be directly associated with a particular disease, although recent studies suggested that TTV may serve as an immunological trigger of multiple sclerosis (26). Similarly, whether TTSuV is associated with a swine disease is still debatable.…”
mentioning
confidence: 99%
“…According to recent studies up to two-thirds or more of the global human population carries anelloviruses in plasma while GBVC can be found in serum of 1-4% of healthy blood donors, with a reported prevalence of 1.2% in The Netherlands (Jongerius et al, 1999;Bendinelli et al, 2001;Praharaj et al, 2006;Maggi and Bendinelli, 2010). These data suggest that the 2 viruses detected in the studied population do not correlate to the onset of schizophrenic symptoms.…”
Section: Discussionmentioning
confidence: 70%
“…TTV10 is a type of anellovirus, a family of viruses with small circular singlestranded DNA genomes that are found in plasma (32)(33)(34)(35). The discovery of BIS8-17 in this patient validates the use of genome amplification techniques to identify new infectious agents from plasma.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, PCR amplification with other general TTV primers may provide more comprehensive detection (37). Additionally, with regard to a specific TTV species, perhaps one of the other 28 TTV species (34,35), other than TTV10 or BIS8-17, may associate with CLL or PV and correlate with disease. Moreover, a TTV containing a specific genomic rearrangement could associate with disease; such a possibility has been entertained for childhood leukemias (45).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation